Systematic review of interventions for improving the performance of community health workers in low-income and middle-income countries. Issue 10 (25th October 2017) - Ballard, Madeleine; Montgomery, Paul
Abstract : Objective: To systematically review and critically appraise the evidence for the effects of interventions to improve the performance of community health workers (CHWs) for community-based primary healthcare in low- and middle-income countries. Design: Systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Methods: 19 electronic databases were searched with a highly sensitive prespecified strategy and the grey literature examined, completed July 2016. Randomised controlled trials evaluating interventions to improve CHW performance in low- and middle-income countries were included and appraised for risk of bias. Outcomes were biological and behavioural patient outcomes (primary), use of health services, quality of care provided by CHWs and CHW retention (secondary). Results: Two reviewers screened 8082 records; 14 evaluations were included. Due to heterogeneity and lack of clear outcome data, no meta-analysis was conducted. Results were presented in a narrative summary. The review found one study showing no effect on the biological outcomes of interest, though these moderate quality data may not be indicative of all biological outcomes. It also found moderate quality evidence of the efficacy of performance improvement interventions for (1) improving behavioural outcomes for patients, (2) improving use of services by increasing the absolute number of patients who access services and, perhaps, better identifying those who would benefit from such services and (3) improving CHW quality of care in terms of upstream measures like completion of prescribed activities and downstream measures like adherence to treatment protocols. Nearly half of studies were compound interventions, making it difficult to isolate the effects of individual performance improvement intervention components, though four specific strategies pertaining to recruitment, supervision, incentivisation and equipment were identified. Conclusions: Variations in recruitment, supervision, incentivisation and equipment may improve CHW performance. Practitioners should, however, assess the relevance and feasibility of these strategies in their health setting prior to implementation. Component selection experiments on a greater range of interventions to improve performance ought to be conducted.